2010
DOI: 10.1093/sleep/33.9.1177
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Aging Effects on Macrovascular and Microcirculatory Function

Abstract: In obesity, both OSA and aging impair endothelial function and increase arterial stiffness. The influence of OSA on vascular function is most pronounced in young subjects. OSA, therefore, may be associated with functional impairment ("a premature aging effect") on the endothelium and on arterial stiffness (in men), although skin microcirculatory function appears preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 40 publications
3
33
1
Order By: Relevance
“…Obesity and aging are probably crucial factors in the United States, and the rising trend of these two factors requires more attention to this context. 17,18 Although the prevalence of risky apnea in the present study was similar to findings in Pakistan (10-12%), 19 it was more common in Malaysia (15.2%). 20 On the other hand, rates if 3.5% and 6.1% were reported in France and Turkey, respectively.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Obesity and aging are probably crucial factors in the United States, and the rising trend of these two factors requires more attention to this context. 17,18 Although the prevalence of risky apnea in the present study was similar to findings in Pakistan (10-12%), 19 it was more common in Malaysia (15.2%). 20 On the other hand, rates if 3.5% and 6.1% were reported in France and Turkey, respectively.…”
Section: Discussionsupporting
confidence: 82%
“…[24][25][26] This has been confirmed in several studies. 1,8,[10][11][12][13]17 For example, obese individuals presented a risk of OSAS that was 10 times higher in the study by Salvador et al 27 There was also a strong relationship between these in the presence of confounding variables. On the basis of several studies, increased body weight can alter the normal upper airway mechanics during sleep through a variety of distinct mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with those from previous studies. [25][26][27][28] Although the 6 risk factors had no further influence on endothelial function after adjusting for covariates, MetS remains a significant and independent determinant of endothelial function.…”
Section: Discussionmentioning
confidence: 93%
“…Yim-Yeh et al 23) reported that both OSA and aging impair the endothelial function and increase arterial stiffness in patients with obesity. Although that study included patients with OSA, the mean patient age was lower (mean age: 40 versus 60 years of age) and the mean BMI was higher (37 kg/m 2 versus 24 kg/m 2 ) than that observed in our population.…”
Section: Resultsmentioning
confidence: 99%
“…The measurement of CAVI has demonstrated good reproducibility and was not affected by the blood pressure during measurement 17,18) . To date, the majority of studies linking OSA to arterial stiffness recruited participants from sleep clinic patients [19][20][21] , there have been only two communitybased studies 22,23) , which also recruited patients with sleep disorder breathing and their methodology to measure arterial stiffness was different to CAVI.…”
Section: Assessment Of Nihmentioning
confidence: 99%